Traduções em prosa da Odisseia de Homero: exemplos e problemas (Nuntius Antiquus, 2014)
My aim is to discuss four Portuguese translations of Homer’s Odyssey. Two were written in prose (by Dias Palmeira/ Alves Correia and by Jaime Bruna), in the 20th century, and two in free verse (by Frederico Lourenço and by Donaldo Schüler), in the 21st century. A quick review of these examples reveals that all of them want to recover Homer’s narrative fluidity, without giving attention to its main formal aspects – which surely enhance the understanding of the contents. As to the latest versions, it is possible to claim that, despite the impressive differences between them, deployment of a free verse betrays the goal of only establishing a line by line correspondence between the original text and the translation, and in the end the principles of a prose translation seem again to guide these versions to Portuguese.